2014
DOI: 10.1111/php.12317
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigations on the Effect of Dermal Fibroblasts on Keratinocyte Responses to Ultraviolet B Radiation

Abstract: Exposure to ultraviolet radiation is closely linked to the development of skin cancers in humans. The ultraviolet B (UVB) radiation wavelength (280-320 nm), in particular, causes DNA damage in epidermal keratinocytes, which are linked to the generation of signature premalignant mutations. Interactions between dermal fibroblasts and keratinocytes play a role in epidermal repair and regeneration after UVB-induced damage. To investigate these processes, established two and three-dimensional culture models were ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…This cross talk between the fibroblasts and keratinocytes involves proliferation and DNA repair of the latter cell type [28] [29]. In this study, we have demonstrated anti-aging and anti-wrinkling potential of BMMSC derived CM using a comprehensive multiparametric analysis by inducing oxidative stress and UV-B damage in dermal fibroblast system in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…This cross talk between the fibroblasts and keratinocytes involves proliferation and DNA repair of the latter cell type [28] [29]. In this study, we have demonstrated anti-aging and anti-wrinkling potential of BMMSC derived CM using a comprehensive multiparametric analysis by inducing oxidative stress and UV-B damage in dermal fibroblast system in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…Human skin equivalents are commonly employed as preclinical models to study, for example, the mechanistic and biological aspects of wound healing, skin sensitizers and the role of ultraviolet (UV) light in DNA damage. [35][36][37] However, it has previously been reported that HSE models develop an overly thick stratum corneum, 15,16 which has important implications for skin research. For example, increased thickness of the stratum corneum can affect the penetration of UV light and, consequently, its biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we describe fibroblast-keratinocyte crosstalk as a modulator of UVB-induced effects in the epidermis (4). Herein, we analysed the effect of IGF-I (as a major pathway in this crosstalk) in (i) the survival, (ii) cell cycle progression, (iii) repair of CPDs and (iv) expression of DNA damage response proteins in irradiated human keratinocytes in vitro.…”
Section: Questions Addressedmentioning
confidence: 99%
“…According to Yoshimura's 'three zones theory' of cell survival, only adipocytes in the most superficial layer (about 300 lm from the graft surface) are in the 'surviving zone', while the rest almost all die within 24 h after transplantation (4). Although the Coleman technique is designed to protect the activity and integrity of the adipocytes, the majority do not survive.…”
Section: Author Contributionmentioning
confidence: 99%